Humans and their technologies play the infinite game - Jouhki, Jukka (Human Technology, 2019)
Technology is increasingly about intuitive use and automation, as is evident to some degree in all the papers published in this issue. Technological–and one could say, even civilizational–progress is made possible by automating necessary but often tedious and tiresome processes. This then frees people’s time and energy for a variety of recreational, inspirational, and/or developmental tasks. However, as the automation of society advances, the meaning of work changes and new existential and ethical questions emerge.